2022
DOI: 10.3390/signals3010002
|View full text |Cite
|
Sign up to set email alerts
|

Wearable Device for Observation of Physical Activity with the Purpose of Patient Monitoring Due to COVID-19

Abstract: In late 2019, a new genre of coronavirus (COVID-19) was first identified in humans in Wuhan, China. In addition to this, COVID-19 spreads through droplets, so quarantine is necessary to halt the spread and to recover physically. This modern urgency creates a critical challenge for the latest technologies to detect and monitor potential patients of this new disease. In this vein, the Internet of Things (IoT) contributes to solving such problems. This paper proposed a wearable device that utilizes real-time moni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…A more recent systematic review has shown that PA improves several health outcomes, including all-cause mortality and cardiovascular diseases [ 2 ]. More recent works also show the benefit of combining PA with other clinically relevant measures, such as temperature, to gain insight into a patient’s health status [ 3 ]. As a measure of PA, step counts derived from digital devices have gained increasing popularity as an objective measure to replace self-reported data [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…A more recent systematic review has shown that PA improves several health outcomes, including all-cause mortality and cardiovascular diseases [ 2 ]. More recent works also show the benefit of combining PA with other clinically relevant measures, such as temperature, to gain insight into a patient’s health status [ 3 ]. As a measure of PA, step counts derived from digital devices have gained increasing popularity as an objective measure to replace self-reported data [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Since older people may present severe side effects and have difficulties moving (absence of public transportation and living in remote areas), there is a need to introduce advanced telemonitoring systems. In recent works, the effectiveness of telemonitoring some physiological parameters has been demonstrated [4,[7][8][9]. The project aims twofold: supporting the families and people with dementia, and showing the efficacy of telemonitoring in a real scenario within the SI4CARE project.…”
Section: Introductionmentioning
confidence: 99%
“…The use of such complex methods is therefore impossible for the intended purpose. Instead, however, it is possible and very easy to use wearable electronics, also called "wearables" [15,16]. Patients with balance disorders are at a higher risk of falling and decompensating their health condition than the healthy population.…”
Section: Introductionmentioning
confidence: 99%